2022
DOI: 10.3390/polym14050889
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Efficient PTB7:PC70BM-Based Polymer Solar Cell for 8% Efficiency

Abstract: Polymer semiconductors may have the potential to fully replace silicon in next-generation solar cells because of their advantages such as cheap cost, lightweight, flexibility, and the ability to be processed for very large area applications. Despite these advantages, polymer solar cells are still facing a certain lack of power-conversion efficiency (PCE), which is essentially required for commercialization. Recently, bulk heterojunction of PTB7:PC70BM as an active layer showed remarkable performance for polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 51 publications
(51 reference statements)
0
25
0
Order By: Relevance
“…SCAPS is a one-dimensional solar cell simulator developed at the department of Electronics and Information Systems (ELIS) of the University of Gent, Belgium. The SCAPS software has been extensively utilized in the modeling and simulation of thin-film devices, including organic and polymer solar cells [ 32 , 33 , 34 , 39 ]. The simulator solves Poisson’s equation, coupled simultaneously with electron and hole continuity equations.…”
Section: Simulation Approach and Solar Cell Structurementioning
confidence: 99%
See 1 more Smart Citation
“…SCAPS is a one-dimensional solar cell simulator developed at the department of Electronics and Information Systems (ELIS) of the University of Gent, Belgium. The SCAPS software has been extensively utilized in the modeling and simulation of thin-film devices, including organic and polymer solar cells [ 32 , 33 , 34 , 39 ]. The simulator solves Poisson’s equation, coupled simultaneously with electron and hole continuity equations.…”
Section: Simulation Approach and Solar Cell Structurementioning
confidence: 99%
“…Incorporating a non-fullerene ITIC acceptor with a PBDB-T donor has been investigated and the optimization of the cell gave an efficiency of 14.25% [ 32 ]. The system ITO/PEDOT:PSS/PT7B:PC70BM/PFN-Br/Ag has been simulated and, upon optimization, a maximum PCE of 8% has been reached [ 33 ]. In [ 34 ], the PTB7:PC 70 BM blend has been explored with different electron transport layer (ETL) materials, and it was found that Zn(O,S) is the most suitable partner, that achieved a PCE of 17.15%.…”
Section: Introductionmentioning
confidence: 99%
“…The whole set of simulation parameters for the designed layers was selected from the literature published in its entirety in [ 36 , 37 , 40 , 41 , 50 , 51 , 52 , 53 , 54 , 55 ]. Numerous material properties must be addressed before simulation, including the donor and acceptor density (N A , N D ), electron and hole mobility (µ n , µ p ), etc.…”
Section: Numerical Modeling Of Devicementioning
confidence: 99%
“…Typically, cells with a PTB7-Th:PC70BM active layer have efficiency between 8% and 9%, 53,54 with a recorded PCE of about 11%. 55 Our cells showed lower efficiency at 5.5%; however, they were optimized for repeatability.…”
Section: Properties Of Solar Cellsmentioning
confidence: 99%